Trichomonas Vaginalis Parasite and its Relationship with Some Inflammatory Cytokines - Ali, Maysaa Younis (Journal of Science in Medicine and Life, 2024)
The parasite Trichomonas vaginalis is a flagellated, anaerobic, single-celled primary parasite that infects the genitourinary tract in humans. It invades the vagina, cervix, and urinary system in women, and the bladder, seminal vesicle, and prostate in men. The symptoms caused by the parasite in women are more pronounced, The Trichomonas vaginalis parasite infects males and females, and the symptoms of the disease in females are more common than in males, and the parasite inhabits the external cavities and halls of humans. The Trichomonas vaginalis parasite is an external parasite that usually lives in the female reproductive system and may be found in the urethra and prostate glands in males. Cytokines are defined as a large group of proteins, including sharks, peptides, glycoproteins, and glycoproteins, which are secreted by certain cells in the immune system. They are produced throughout the body by various indigenous cells. The high levels of chemotactic protein for monocytes in the group of people infected with the symptomatic Trichomonas vaginalis parasite is due to the host’s response to parasite antigens and the activation of chemotactic protein-generating cells, which are mast cells. It is known that mast cells quickly secrete powerful inflammatory mediators such as chemokines and histamine in response to infection with the Trichomonas parasite Vaginal. Whoconfirmed that Trichomonas vaginaliscauses significant increase in IL-6concentration of patients' serum comparison to the control group. Another study showed that human neutrophils or macrophages stimulated with live T.vaginalis produce the chemokine interleukin (IL-8) and the proinflammatory cytokines tumor necrosis factor-x, IL-6 and IL-1β.